The impact of multiple supports on university students’ physical education learning motivation: a dual analysis based on SEM and fsQCA - Hao, Huaixia; Zhu, Qingying; Feng, Changxi (Frontiers in Psychology, 2025)
BackgroundDuring their physical education courses, university students may encounter various academic pressures and difficulties, which significantly undermine their physical education learning motivation and affect their overall development. Multiple supports from teachers, parents, and peers can effectively help students maintain confidence and enhance their physical education learning motivation. However, the underlying mechanisms by which these multiple supports influence motivation for physical education remain unclear.ObjectiveThis study aims to explore the underlying mechanisms by which multiple supports influence learning motivation during physical education, specifically examining the mediating roles of self-efficacy and positive coping style. Additionally, it seeks to elucidate the complex configurational relationships among multiple supports, self-efficacy, coping style, and physical education learning motivation.MethodsThis study employs a cross-sectional survey method to investigate Chinese university students. Through convenience sampling, 969 students were recruited from four universities in Shandong Province. The participants completed the Teacher Support Scale, Parent Support Scale, Peer Support Scale, Self-Efficacy Scale, Positive Coping Style Scale, and Learning Motivation Scale. For data analysis, statistical processing was conducted using SPSS 26.0, Amos 22.0, and fsQCA 4.1.ResultsThe results indicate that multiple supports from teachers, parents, and peers have significant direct effects on individual physical education learning motivation, with effect sizes of 0.132, 0.090, and 0.237, respectively. Self-efficacy acts as an independent mediator between multiple supports and physical education learning motivation, with effect sizes of 0.111, 0.076, and 0.197, respectively. Positive coping style also serve as an independent mediator in these relationships, with effect sizes of 0.091, 0.019, and 0.072; Self-efficacy and positive coping style function as a chain mediating mechanism between multiple supports and physical education learning motivation, with effect sizes of 0.021, 0.015, and 0.038; There are five equivalent configurations identified among multiple supports, self-efficacy, coping style, and physical education learning motivation.ConclusionSupport from teachers, parents, and peers not only directly influences students’ physical education learning motivation but also indirectly predicts students’ physical education learning motivation through the independent and chain mediating roles of self-efficacy and coping style. Additionally, this study elucidates the complex configurational relationships among multiple supports, self-efficacy, coping style, and physical education learning motivation, thereby validating and supplementing the results of linear analysis.